Cardiac output measurement. Issue 2 (February 2016) - Gilbert, Michael
Abstract: Cardiac output measurement is used to guide fluid and inotropic drug therapy. Techniques employ modelling of the circulation to derive estimates of cardiac output from readily measured variables, including thermodilution, analysis of arterial pressure waveforms, Doppler measurements of blood flow velocity, and electrical bioimpedance.